A fiber optic communication shield based on a two-dimensional molybdenum disulfide broadband absorber. (September 2022) - Li, Rui; Pan, Miao; Yi, Zao; Yu, Jiaxin; Shi, Pengcheng; Luo, Hao; Wu, Pinghui; Yang, Hua; Wang, Shifa; Gao, Guocheng
Graphical abstract: Highlights: Perfect broadband absorption at 1550 nm, the most important band for fiber optic communication. This absorber structure is widely used for perfect absorbers based on transition-metal dichalcogenides (TMDCs) materials. An effective method for tuning molybdenum disulfide-based absorbers is proposed. The physical mechanism of the high absorption of the molybdenum disulfide layer is well discussed. Abstract: We propose a broadband absorber in the infrared band using a two-dimensional molybdenum disulfide with a patterned gold array. The light absorption enhancement effect of the local surface plasmon resonance (LSPR) is utilized to greatly enhance the light absorption of the monolayer MoS2 . Our absorber has 99.62% absorption in the most important band for fiber optic communication (i.e. 1550 nm), a result calculated by the finite-difference time-domain method. Our absorber can serve as an excellent shield for fiber optic communication. At the same time, our absorber is also polarization and light incidence angle insensitive, which greatly expands the application location of our absorber. In addition, we demonstrate that our absorber structure can be widely used in absorbers based on transition-metal dichalcogenides (TMDCs), which is a guideline for the design of such absorbers. In order to solve the tuning difficulties of MoS2 -based absorbers, we also propose an effective method for tuning the absorber, which is able to tune the absorber over a large wavelength range without a significant decrease in the absorber's optical absorption. We believe that our absorber can play an important role in fiber optic communication shielding systems, detection systems in the infrared band.